Perancangan Busana Avant Garde dengan Inspirasi Bunga Titan Arum - Lie, Sherly Sanjaya; Renaningtyas, Luri; Yessica, Evania (BAJU: Journal of Fashion and Textile Design Unesa, 2024)
Fashion in Indonesia is also increasing, where fashion itself is used as a means of self-expression which is through avant garde.  The need for avant garde fashion itself is quite increasing, but avant garde fashion designers are still rarely found in Indonesia. Avant garde fashion has become a necessity, especially in the showbiz sector, such as artists and influencers who need attention from the public through unique and attractive clothing. In line with the concept of avant garde fashion, this fashion collection inspired by Indonesian flora Titan Arum which has a quite unique shape. The Titan Arum flower is a type of corpse flower native to Indonesia whose existence is threatened and is still protected. Based on the government's efforts to preserve Indonesian flora, this design highlights the Titan Arum flower as an inspiration and also to increase awareness of Indonesia's endangered flora. Based on these problems, this design adopts an avant garde concept which has a unique form of meeting fashion needs in Indonesia as well as attracting the public to increase public interest in Indonesia's endangered flora. The method used in this design is design thinking and qualitative methods by collecting data through books, news, interviews, and so on.